Β-carboline alkaloids attenuate bleomycin induced pulmonary fibrosis in mice through inhibiting NF-kb/p65 phosphorylation and epithelial-mesenchymal transition. (28th October 2019) - Cui, Yulei; Jiang, Lei; Yu, Ruitao; Shao, Yun; Mei, Lijuan; Tao, Yanduo
Abstract: Ethnopharmacological relevance: The plant Arenaria kansuensis is used in traditional medicine to treat lung inflammation for a long time. However, the anti-pulmonary fibrosis effect and its corresponding bioactive constituents of this plant have not been studied extensively. Aim of the study: The purpose of this study was to investigate the anti-pulmonary fibrosis effect and its corresponding bioactive constituents of A. kansuensis and its possible mechanism. Materials and methods: In vivo experiment, the anti-pulmonary fibrosis effects of the fraction (Part1 ) enriched from ethyl acetate extracts of the whole plant A. kansuensis were evaluated through bleomycin (BLM)-induced pulmonary fibrosis mice (five groups, n = 10) daily at doses of 50, 100 and 150 mg/kg for 15 days. In vitro experiment, the anti-inflammation and reversed epithelial-mesenchymal transition (EMT) effect of 12 β-carboline alkaloids isolated from Part1 were evaluated through lipopolysaccharide (LPS)-induced RAW264.7 inflammatory cell model and TGF-β1 induced A549 cell model. Results: In this study, a fraction named Part1 extracted from Arenaria kansuensis presented strong anti-pulmonary fibrosis effect at the dose of 150 mg/kg. Vivo experiments showed that the survival rate and body weight of mice significantly increased after Part1 treatment. Part1 could significantly inhibit the initial of inflammation, deposition of collagen and expression of TGF-β1 and α-SMA, moreover, the expression of E-cadherin was significantly elevated after administration of Part1 . All the cure effects of Part1 were in dose dependent manner. A total of 12 β-carboline alkaloids were identified in Part1 and they all showed suppressive effect on inflammatory cytokines including MCP-1, TNF-α, IL-6 and IL-1β through inhibition of NF-kb/p65 phosphorylation, and that epithelial-mesenchymal transition (EMT) process was reversed by different compounds in different levels. The expression of indicators of EMT including α-SMA, vimentin and E-cadherin was significantly improved after given different β-carboline alkaloids. Conclusions: This study showed that antifibrogenic effect of β-carboline alkaloids was due to inhibiting the initial of inflammation through NF-kb/p65 pathway and reversing the process of EMT. Graphical abstract: Image 1